The Effect of Drying Methods and Extraction Techniques on Oleuropein Content in Olive Leaves - Darija Cör Andrejč; Bojan Butinar; Željko Knez; Kaja Tomažič; Maša Knez Marevci (Plants, 2022)
Increased demand for olive oil has caused higher quantities of byproducts in olive processing, such as olive leaves, olive skins, and vegetation water. It is well known that olive leaves contain several phenolic compounds, including secoiridoids. Oleuropein is the major secoiridoid in olive leaves. Oleuropein has been found to exhibit antioxidative, antimicrobial, antiviral, and antiatherogenic activities. We studied the effect of extraction techniques and drying methods on oleuropein content in olive leaves of Istrska belica and Lecino cultivar. Three different procedures of drying were used: at room temperature, at 105 °C, and freeze drying. Ethanol-modified supercritical extraction with carbon dioxide, conventional methanol extraction, and ultrasonic extraction with deep eutectic solvent were performed. Antioxidant activity was determined, as well as methanolic and supercritical extracts. The presence of olive polyphenols was confirmed by the HPLC method.